Heat pulse velocity method for determining water requirements in rainfed sweet cherry trees (Prunus avium L.) - Tharaga, Phumudzo C.; Tesfuhuney, Weldemichael A.; Coetzer, Gesine M.; Savage, Michael J. (Frontiers in Horticulture, 2023)
There is a paucity of knowledge regarding the soil water use under stress conditions of sweet cherry. This study investigates the water use of sweet cherry using the heat pulse velocity sap flow method. Tree response to drying soil conditions over two consecutive measurement periods (September 2017 to December 2018) in the eastern Free State, South Africa, is also evaluated. During the post-harvest period (December), there was a continuous increase in daily water consumption by trees, in conjunction with an increase in canopy cover, even though the crop load was reduced. Measured sap flow was positively correlated to net radiation, air temperature, and water vapour pressure deficit. The transpiration rates ranged from 1.2 to 3.5 L d-1 during the flowering stage (day of year, DOY, 244 – 270) and showed an increasing trend as the days progressed. During the ripening stage (DOY 271 – 292), transpiration rates decreased from 4.5 to 1.1 L d-1 over the 2018 season. This decreasing trend from the previous growth stage was due to soil drying and scorching weather conditions that led to trees experiencing water stress. Sap flow measurements, however, showed typical characteristics of the diurnal trend during selected days during varying weather conditions. The fraction of transpirable soil water (FTSW) threshold varied for different fruit growth stages and approached 1.0 for different stress levels. FTSW exceeded ~0.4 when sweet cherry trees utilised stored soil water, while the transpiration rates declined during prolonged hot days. Moreover, the stress coefficient factor ranged between 0.45 – 0.65 for different growth stages. The daily soil water content varied, and soil evaporation was expected to increase during hot and dry days. In the early stage of a dry spell, soil water content did not directly affect the transpiration rate. Sweet cherry trees are susceptible to soil water deficit at different stages of fruit development. More research is required to understand transpiration as an irrigation management and planning indicator.